Soil Investigation for Determining Aquifer Position at PasirImpun Area, Bandung, West Java Using Resistivity Method Wenner Configuration - Parwatiningtyas, Diyan; , Dasmo; Sjamsuri, Achmad (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
At this time, we owning many geophysics methods that can be used to optimize investigation and natural source exploration under layer surface, one of them isGeoresistivity method. Georesistivity method is one of geophysics method that study about electricity in the earth and also to detect an object in the surface layer area of earth. The following, a technology is showed to investigation and analyzed aquifer at botanical garden area, Mekarmanik village, PasirImpun, East Bandung West Java, using Georesistivity method, Wenner Configuration. In this research, will be do Georesistivity method with Wenner configuration and be processed with using inversion from software Res2DIV, and Isopach aquifer contour mapping, which previous be done the topography correction. Based on the inversion obtained, we be obtain to interpret some points which showed aquifer position, are as follow : 1). Line 1 on location 1, with the distance of extend is between 78 – 140 metre on surface layer. (It has medium aquifer) which the resistivity is 800 ohm metre, and also has porosity and volum value 25% and 945,9 m3 with the depth is 60 metre. Its formation rocks at this location are sandstone, and limestone, anticline topography, dominated by normal fault which the trend is NE-SW. 2). Line 6 on location 1 (The highest aquifer) with the distance of extend is between 26 – 182 metre 26 - 160 metre, which the resistivity is 100 – 300 ohm metre, porosity and volum value are 14,14 – 18,26% and 1160,85 m3, with the depth target is 70 metre. Its formation rocks at this location are sandstone, alluvial and limestone, syncline topography, dominated by normal fault which the trend is NE-SW. And then the third is line 8 on location 2 with the distance of extend is between 26 – 182 metre, the resistivity is 100 ohm metre, which its porosity and volum are 14,14 %, and 264 m3, with depth target is 35 metre. It has undulation topography which the trend is SE – SW dominated by normal fault, and its formation rocks are tuff, sandstone, gravel formation.